Experiencing risk: higher-order risk attitudes in description- and experience-based decisions [dataset] - Becker, Christoph; Ert, Eyal; Trautmann, Stefan T.; Kuilen, Gijs van de (Universität, 2021)
Risky decisions are often characterized by (a) imprecision about consequences and their likelihoods that can be reduced by information collection, ...
Gesehen am 04.08.2021
Keywords: Forschungsdaten; Datenbank